COPING NARRATION THROUGH THE PANDEMIC: X (EX-TWITTER) ANALYSES OF PSYCHOSOCIAL RESPONSES TOWARDS THE IMPACT OF COVID-19 AMONG INDONESIANS - Muhiddin, Syurawasti; Saefudin, Muhamad Arif; Afifah, Yasmin Nur; Thontowi, Haidar Buldan (Interaksi: Jurnal Ilmu Komunikasi, 2024)
This study utilized Twitter data to examine narratives related to psychosocial responses to the impacts of COVID-19 among Indonesians, which were further discussed in the context of coping strategies. We collected and analyzed tweets containing coping-related trending hashtags, namely #Covid-19, #coronavirus, #lockdown, #dirumahsaja (stay at home), #newnormal, #pakaimasker (wear a mask), #amandirumah (safe at home), #vaksin (vaccine), #ppkm (referring to the micro-lockdown term), #coping, and the keyword “mental health.” A total of 24,502 tweets were collected from three distinct periods: the Early COVID-19 Emergency Responses Phase, the New Habit Adaptation Phase, and the Early Mass Vaccination Phase, using a Python-based library. After filtering out duplicate and irrelevant tweets, a total of 6,265 tweets were subjected to deductive content analysis procedures. This study found that Indonesian Twitter users more often tweeted narration related to problem-focused coping strategies during the three periods of COVID-19 in Indonesia, followed by seeking social support in the first and the third periods, while cognitive coping was the second most strategy in the second period. Informational sharing, problem-solving strategies, and criticism were the three most forms of problem-focused coping strategy. Calls or appeals and social support seeking was the most form of social coping strategies. The forms of cognitive coping were finding meaning or reflection, views, and optimism. This study implies the exploration of the speech-act psychology, the intersection of psychology, communication, and even technology to understand how individuals and communities adapt to crises. The findings also inform public health communication strategies, social media governance, and mental health interventions aimed at mitigating the impacts of crises.